2020
DOI: 10.3748/wjg.v26.i28.4140
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor substrate 1 may play divergent roles in human colorectal cancer development and progression

Abstract: BACKGROUND Despite effective prevention and screening methods, the incidence and mortality rates associated with colorectal cancer (CRC) are still high. Insulin receptor substrate 1 (IRS-1), a signaling molecule involved in cell proliferation, survival and metabolic responses has been implicated in carcinogenic processes in various cellular and animal models. However, the role of IRS-1 in CRC biology and its value as a clinical CRC biomarker has not been well defined. AIM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Liao et al [ 33 ] established a kNN classification model based on the clinicopathological information and protein expression profile analysis of CRC, which predicted the degree of tumor differentiation of CRC with high accuracy ( P ≤ 0.001, receiver-operator characteristics-ROC-error, 0.171). The expression of related genes, such as HER3 and insulin receptor substrate 1, was found to be a predictive target of the degree of CRC differentiation [ 34 , 35 ]. Metabolites from gut microbes also play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Liao et al [ 33 ] established a kNN classification model based on the clinicopathological information and protein expression profile analysis of CRC, which predicted the degree of tumor differentiation of CRC with high accuracy ( P ≤ 0.001, receiver-operator characteristics-ROC-error, 0.171). The expression of related genes, such as HER3 and insulin receptor substrate 1, was found to be a predictive target of the degree of CRC differentiation [ 34 , 35 ]. Metabolites from gut microbes also play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been shown that IGF-1 receptor (IGF-1R) is overexpressed in CRC [28,46] and it is well established that the association of IGF-1 with its receptor stimulates cell proliferation and survival thus contributing to cancer development [28]. In addition, it was demonstrated that insulin receptor substrate-1, as the principal cellular effector of IGF-1R, is also overexpressed in CRC tissue [47,48], although a recent study by Lomperta et al [49] suggested a possibility of its divergent roles in the regulation of apoptosis. Furthermore, activation of the IGF-1/IGF-1R pathway can be at least partly responsible for CRC treatment resistance [28].…”
Section: Insulin Resistancementioning
confidence: 99%
“…IRS-1 and IRS-2 are widely expressed in humans and are, therefore, the most studied proteins in the family [ 3 ]. There is a relationship between IRS-1 and 2 and various types of cancer, such as breast [ 4 , 5 , 6 , 7 , 8 ], lung [ 9 ], prostate [ 10 ], hepatocarcinoma [ 11 , 12 , 13 ], neuroblastoma [ 14 , 15 ], head and neck [ 16 ], colorectal [ 17 , 18 ], esophageal squamous cell carcinoma [ 19 ], non-small cell lung cancer [ 20 ], and glioblastoma multiforme [ 21 ]. It has been observed that the expression and function of the IRS may vary in the different types of cancer.…”
Section: Introductionmentioning
confidence: 99%